# HELP: Differential Calculus

• Jul 17th 2010, 06:25 AM
copyninja1991
HELP: Differential Calculus
hey! (Bow)
can anyone help me how to get the derivative of an equation?? any equation! PLEASE show me how! you may give your own example but PLEASE do it step by step so I may understand...

(Worried) Thanks! That derivative thing is driving me nuts!
• Jul 17th 2010, 06:46 AM
Krizalid
it's not a long way to learn it but, you'll need lots of properties that your brain's gonna have to eat.

perhaps, do you have any examples so that we can start from basics?
• Jul 17th 2010, 06:55 AM
copyninja1991
here's a function.. please show me how..

f(x) = 3x²-2x+4

btw, there's this RULES ON DERIVATIVES, can you give me any shortcut how to familiarize with them easily?? i'm really bad at familiarizing, worse memorizing things.. i really forget thing easily..
• Jul 17th 2010, 07:18 AM
Prove It
The derivative of any function $\displaystyle f(x)$ is

$\displaystyle f'(x) = \lim_{h \to 0}\frac{f(x + h) - f(x)}{h}$.

The calculation of this limit (known as finding the derivative by first principles) can be long and tedious. Thankfully, in many cases the derivative of a function can be found using a rule.

First: The derivative of a sum/difference of functions is the sum/difference of the functions' derivatives.

For a polynomial $\displaystyle f(x) = ax^n$, the derivative $\displaystyle f'(x) = nax^{n-1}$. You could think of this as "multiplying the coefficient by the power, then subtracting $\displaystyle 1$ from the power".

$\displaystyle f(x) = 3x^2 - 2x + 4$

First principles:

$\displaystyle f'(x) = \lim_{h \to 0}\frac{f(x+h) - f(x)}{h}$

$\displaystyle = \lim_{h \to 0}\frac{3(x + h)^2 - 2(x + h) + 4 - (3x^2 - 2x + 4)}{h}$

$\displaystyle = \lim_{h \to 0}\frac{3x^2 + 6xh + h^2 - 2x - 2h + 4 - (3x^2 - 2x + 4)}{h}$

$\displaystyle = \lim_{h \to 0}\frac{6xh + h^2 - 2h}{h}$

$\displaystyle = \lim_{h \to 0}(6x + h - 2)$

$\displaystyle = 6x - 2$.

Using the rule: Evaluate the derivative of each term using the rule.

$\displaystyle f(x) = 3x^2 - 2x + 4$

$\displaystyle = 3x^2 - 2x^1 + 4x^0$.

$\displaystyle f'(x) = 2\cdot 3x^{2-1} - 1\cdot 2x^{1-1} + 0\cdot 4x^{0-1}$

$\displaystyle = 6x - 2$.

As you can see, using the rule is much easier than using first principles.
• Jul 17th 2010, 10:44 AM
HallsofIvy
Quote:

Originally Posted by copyninja1991
here's a function.. please show me how..

f(x) = 3x²-2x+4

btw, there's this RULES ON DERIVATIVES, can you give me any shortcut how to familiarize with them easily?? i'm really bad at familiarizing, worse memorizing things.. i really forget thing easily..

You memorize things well by using them again and again- work lots of problems.
• Jul 17th 2010, 02:36 PM
mr fantastic
Quote:

Originally Posted by copyninja1991
hey! (Bow)
can anyone help me how to get the derivative of an equation?? any equation! PLEASE show me how! you may give your own example but PLEASE do it step by step so I may understand...

(Worried) Thanks! That derivative thing is driving me nuts!

Don't you have class notes or a textbook?